Extraction and purification of antioxidative flavonoids from Chionanthus retusa leaf - Wang, Zhen; Yang, Shilong; Gao, Yajun; Huang, Jianting (Frontiers in Bioengineering and Biotechnology, 2022)
In this work, the flavonoids in Chionanthus retusa leaves were extracted by alcohol using single-factor and orthogonal experiments to optimize the extraction yield. Then, the extracted solution with flavonoids was purified via macroporous resin by eluting with different concentrations of ethanol. The antioxidative activity of total flavonoid in purified extracted solution was evaluated by detection the ability to scavenge DPPH free radicals. The results demonstated that the ethanol with concentration of 60%, ultrasonic power of 140 W, liquid-solid ratio of 25:1 mL•g-1, and water bath temperature of 80 °C were the optimum conditions for the extraction of total flavonoids from Chionanthus retusa leaves, which could achieve the yield of 121.28 mg•g-1. After purification by the macroporous resin using different concentration of ethanol, a highest content of total flavonoids (88.51%) in the extracted solution can be obtained from 50% ethanol eluant. The results of scavenging DPPH free radicals suggested that the purified flavonoids in 50% ethanol eluant showed best antioxidant capacity than that of the flavonoids in other ethanol eluant. In addition, it is confirmed the antioxidant capacity of the extractives was associated with the content of total flavonoids and kinds of flavonoids. These results may provide a project to make full use of total flavonoids from Chionanthus retusa leaves.